Elevation-dependent variations of tree growth and intrinsic water-use efficiency in Schrenk spruce (Picea schrenkiana) in the western Tianshan Mountains, China - Wu, Guoju (Front Plant Sci, 2015)
Rising atmospheric CO(2) concentration (C(a)) is expected to accelerate tree growth by enhancing photosynthesis and increasing intrinsic water-use efficiency (iWUE). However, the extent of this effect on long-term iWUE and its interactions with climate remains unclear in trees along an elevation gradient. Therefore, we investigated the variation in the radial growth and iWUE of mature Picea schrenkiana trees located in the upper tree-line (A1: 2700 m a.s.l.), middle elevation (A2: 2400 m a.s.l.), and lower forest limit (A3: 2200 m a.s.l.), in relation to the rising C(a) and changing climate in the Wusun Mountains of northwestern China, based on the basal area increment (BAI) and tree-ring δ(13)C chronologies from 1960 to 2010. We used the CRU TS3.22 dataset to analyze the general response of tree growth to interannual variability of regional climate, and found that BAI and δ(13)C are less sensitive to climate at A1 than at A2 and A3. The temporal trends of iWUE were calculated under three theoretical scenarios, as a baseline for interpreting the observed gas exchange at increasing C(a). We found that iWUE increased by 12–32% from A1 to A3 over the last 50 years, and showed an elevation-dependent variation in physiological response. The significant negative relationship between BAI and iWUE at A2 and A3 showed that tree growth has been decreasing despite long-term increases in iWUE. However, BAI remained largely stable throughout the study period despite the strongest iWUE increase [at constant intercellular CO(2) concentration (C(i)) before 1980] at A1. Our results indicate a drought-induced limitation of tree growth response to rising CO(2) at lower elevations, and no apparent change in tree growth and diminished iWUE improvement since 1980 in the upper tree-line. This study may contradict the expectation that combined effects of elevated C(a) and rising temperatures have increased forest productivity, especially in high-elevation forests.